Tipologias de perfis de empregados a partir do significado do trabalho e da realização de valores pessoais: um estudo em uma organização bancária - Sivieri, Ana Cláudia Gentil (2016)
This study aimed at identifying types of employees’ profiles of a national banking organization from the Meaning of Work and Personal Values Realization in the organizational environment – PVR. The assumption is that organizations are not mere environments where it draws sustenance, but spaces that enable the realization of the covering both the concrete aspect of materializing a task, how to develop a process of identity and personal story based on the experience social which, over time, relations and impacts meaning of work. This entire process has been valued by organizations, especially after the productive restructuring that took place from the twentieth century, who brought the concept of human capital. Thus, individual perceptions need to be known and understood. The Meaning of Work is the subject that has developed as a scientific research object from the work of the Meaning of Working Group (MOW, 1987). One of the most relevant studies in Brazil based on the MOW was carried out by Borges (1998b), who drafted the model adopted in this study, treating the meaning of work as a subjective and social cognition, influenced by socio-historical aspects. Already the RVP construct (MAURINO, DOMENICO, 2012) seeks to measure the perception of fair values people in the workplace, the main basis of the theory of Schwartz values (1992). This research, survey type was performed by use of two questionnaires: Inventory Labor Meaning, adapted for this research, and the Inventory of Personal Values Realization in the organizational environment. The liquid sample included 2,649 respondents, most married men, averaging 40 years. Data analysis was performed by multivariate statistical techniques. The results showed high absolute centrality of work, that is, the level of importance of the work, bringing the work as the second most important sphere of life, preceded by the family. Employees of the bank aims to working conditions, self-fulfillment and self-development, however, describe the concrete work as a source of security, which demands responsibility, commitment and agility in the face of everyday activities. In addition, they realize the routine wear and pressure as associated to the work. Mostly, they realize Self-Transcendence values, which show the highest scores. Data analysis also allowed to raise a hypothesis for future research, which verifies the existence of a positive relationship between centrality of work and RVP. To identify the types, we used the cluster analysis technique, resulting in three clusters, typified as Engajed, Responsible and Critic Persons.